Bibliometric analysis of the research on hydrogen economy: An analysis of current findings and roadmap ahead. (5th March 2022) - Kar, Sanjay Kumar; Harichandan, Sidhartha; Roy, Biswajit
Abstract: Based on literature research, this comprehensive analysis of 1275 articles published in the past five decades provides quantitative and objective insight into research trends in the hydrogen economy. Scholars and experts agree that by 2030, hydrogen will play a critical role in energy transition by complementing other renewable energy technologies. We applied indicators such as the Field-Weighted Citation Impact index, cited by and usage count (180 days) to evaluate countries, authors, documents, journals and so on. We also used VOS viewer to visualize the evolving trend using keyword analysis and cluster analysis of documents. Results show that the literature on the hydrogen economy has been recently increasing, particularly from 2016 to 2020. Scopus database was employed to acquire the required data for the study. From preliminary analysis, it was established that from 218 journals, 1275 documents related to hydrogen economy had been published so far. The average publication per year since introducing the term "hydrogen economy" is 6.62 and increasing. The average citation per document is 47.21. There have been 3760 authors so far who have been associated with publications related to a hydrogen economy. Of which 139 authors have written 156 documents individually, and 3621 authors have collaborated to publish 1119 documents, thus forming a collaborative index of 3.24. The International Journal of Hydrogen Energy contributes 40% of the overall publications. In terms of countries, China and United States are the leaders, with 126 papers each. Our analysis shows that the study on hydrogen economy mostly deals with multidisciplinary aspects like hydrogen production, storage, transportation, application, and public policy formulation. We adopted the 180 days usage count offered by the Web of Science database to better understand the research hotspot and evolving trends. It helped us view the existing gaps and potential scope of study that future researchers working on the hydrogen economy can explore. Aspects like pipeline transportation, risk assessment studies, blending, public safety and hazard mitigation can play a vital role in the hydrogen economy research in the future. Cooperation between nations and research institutes should be fostered with cross-disciplinary interchange to boost the hydrogen economy's multidisciplinary growth. Highlights: Bibliometric analysis reveals International Journal of Hydrogen Energy is the pioneer journal on hydrogen economy. Network visualisation analyses disclose that there is a high collaboration index (3.24) among authors. USA and China are the leaders with 10% publication each. Emphasis is needed on pipeline transportation, risk assessment studies, and hydrogen blending research. Hydrogen supply chain and hydrogen fuel cell were the prime themes.